Grown up - Tan, Chloe (Nanyang Technological University, 2020)
Grown Up is a light-hearted, educational game application that aims to help youths transit into adulthood. Many of us may be caught up with the present that we do not realize the importance of preparing for what is to come. This game serves as a steppingstone by placing players into situations such as job hunting, work-life balance, savings, and all things grown-up!